Effects of high dose atorvastatin before elective percutaneous coronary intervention on highly sensitive troponin T and one year major cardiovascular events; a randomized clinical trial. (March 2019) - Pourhosseini, HamidReza; Lashkari, Reza; Aminorroaya, Arya; Soltani, Danesh; Jalali, Arash; Tajdini, Masih
Abstract: Introduction: Some studies have demonstrated that post-PCI elevated cardiac enzymes are associated with worse outcomes. In this study, we aimed to determine if high-dose treatment with atorvastatin before planned elective PCI reduces PMI or MACE at 1-year median follow-up. Material and methods: Eligible participants were randomly allocated to group A (80 mg atorvastatin 12 h and 40 mg 2 h before PCI) and group B (40 mg atorvastatin daily). Blood samples were obtained before and at 24 h after PCI to measure hsTnT. All patients were followed regarding MACE (combination of death, re-hospitalizations for ACS, and unplanned coronary revascularization) during one year after PCI. Results: 207 patients randomly assigned to Group A (n = 97) or group B (n = 110). The rate of PMI was lower in group A (5.2%) compared to group B (10.9%); despite near to 50% lower rate of PMI in group A, binary logistic regression showed no significant association between atorvastatin recapture and PMI. The occurrence of MACE in 97 patients of group A was 11 (11.3%), higher than 11 (10%) cases of 110 patients in group B. Cox proportional hazards regression model shows no significant difference in MACE of study groups. Conclusion: Pretreatment of patients with stable angina who were planned to undergo an elective PCI with 120 mg of atorvastatin before the procedure confer them the same benefit in terms of PMI and MACE as 40 mg routine daily dosage of this statin does.